Accelerated ageing tests of sodium chloride for the evaluation of stones durability to salt crystallization: A comparative study of selected restoration lithotypes. (September 2022) - Galanaki, Niki; Delegou, Ekaterini; Bris, Theodore; Moropoulou, Antonia
Abstract: This work presents the assessment of the susceptibility of five different lithotypes to salt crystallization decay, after the application of accelerated ageing tests of NaCl solution by total immersion, and duration of 60 days. Particularly, four different biocalcarenites (Rhodes Greece, Spain and Cyprus), and a calcitic sandstone (Achaia Greece) are investigated. Their durability to salt decay is evaluated by performing mass change measurements, total immersion tests, and the non-destructive techniques of Digital Microscopy, Ultrasound Pulse Velocity, and Colorimetry. It is demonstrated that the Cyprus biocalcarenite, followed by the calcitic sandstone, exhibit the lowest durability to NaCl crystallization decay among the investigated lithotypes. Finally, considering the results of this study with previously published data, it can be concluded that pore size distribution and in particularly the percentage of the pores with radii above 10 μm plays a key role in the susceptibility that the investigated lithotypes exhibit to NaCl crystallization damage. Highlights: Susceptibility assessment of five different lithotypes to salt crystallization decay. Ageing test cycles of subsequent specimens' immersion in NaCl solution for 60 days. All the examined lithotypes degraded severely, but to a different extent. Cyprus biocalcarenite and the calcitic sandstone exhibit the lowest durability. Pore size distribution is the key parameter in stone susceptibility to salt decay.